The multifaceted relationship between land and violent conflict: the case of Apaa evictions in Amuru district, northern Uganda. Issue 3 (11th August 2017) - Kobusingye, Doreen Nancy; van Leeuwen, Mathijs; van Dijk, Han
ABSTRACT: This paper argues that violent conflict prominently impacts on land governance and so contributes to land conflicts in post-conflict settings. In the natural resources literature, the relationship between land and conflict is often explained in terms of environmental security or political ecology, and many have pointed out that the way land is governed in itself may be a source of conflict. However, less attention has been given to the effects of violent conflict on land and its governance in post-conflict situations. This paper argues that violent conflict affects land governance in many ways and that this in turn might contribute to further violent conflict. The argument builds around an extended case study of the Apaa evictions in Amuru District in Northern Uganda. The case illustrates how conflict around land is not just the result of resource scarcity and competition, but is the outcome of a combination of political, historical and social dynamics. Past policies on land and practices of land governance play a critical role in this. However at the same time, violent conflict has a critical impact on land access, transforms land governance authority and the rules applied. The land conflicts resulting from this, in turn, fuel ethnic tensions between local population groups, and grievances about those in power and the institutions that govern natural resources. The ways in which such problematic conflict-induced changes in land access and governance are dealt with by policymakers is critical for post-conflict stability.